Self‐Trapped Exciton to Dopant Energy Transfer in Rare Earth Doped Lead‐Free Double Perovskite. Issue 23 (18th September 2019) - Li, Shunran; Hu, Qingsong; Luo, Jiajun; Jin, Tong; Liu, Jing; Li, Jinghui; Tan, Zhifang; Han, Yibo; Zheng, Zhi; Zhai, Tianyou; Song, Haisheng; Gao, Liang; et al.
Abstract: Low dimensional halide perovskites with self‐trapped excitons (STEs) emission have emerged as promising white light phosphors because of their ultrabroadband emission covering the entire visible spectrum from 400 to 800 nm. Such a broad emission from a single material can overcome emission color change and self‐absorption problems within multiple phosphors. However, the color rendering index (CRI) and correlated color temperature (CCT) as two essential parameters of white light quality can hardly be modulated in these perovskite materials. Here, rare earth ion Ho 3+ is introduced into Cs2 (Na, Ag)InCl6 for the first time, utilizing the hydrothermal method. Besides the strong warm white STEs emission, the as‐synthesized materials exhibit effective characteristic emission of Ho 3+ in the visible region. Further, the mechanism of associated emission is explored and the existence of energy transfer from STEs to rare earth is first confirmed. A white light‐emitting diode (LED) prototype is also fabricated by employing the Ho 3+ doped Cs2 (Na, Ag)InCl6 as the color conversion material on a commercial 365 nm GaN LED chip, achieving an improved CRI from 70.3 to 75.4 compared to the pure Cs2 (Na, Ag)InCl6 . This result suggests a promising way to achieve high quality single phase all‐inorganic white phosphors and this mechanism has enormous potentials in other optoelectronic applications. Abstract : Here, Ho 3+ doped CNAIC is synthesized via the hydrothermal method for the first time. The doped double perovskite combines efficient self‐trapped exciton (STE) and rare earth associated emission. Furthermore, by means of infrared spectrum and photoluminescence (PL) decay, the associated emission mechanism is explored and the existence of the energy transfer channel from STEs to Ho 3+ is confirmed.